PELAYANAN PUBLIK BERBASIS DIGITAL MELALUI PROGRAM “PANAH SRIKANDI” (PELAYANAN RAMAH SISTEM REGISTRASI ADMINISTRASI KEPENDUDUKAN DESA INTEGRASI): (Studi di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bojonegoro) - Ayu Pradita, Nadia Anggie; Sumartono, Sumartono; Amin, Fadillah (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2025)
This study aims to describe the implementation of digital-based public services through the PANAH SRIKANDI program at the Department of Population and Civil Registration of Bojonegoro Regency, identify and analyze the supporting and inhibiting factors in the program’s implementation, and evaluate the effectiveness and efficiency of PANAH SRIKANDI in improving the accessibility and quality of civil administration services at the village level. Employing a descriptive qualitative case study approach, the research focuses on five key pillars of e-Government by Indrajit (2006): e-Vision, Governance, Strategies and Policies, Resource Commitment, and Service Effectiveness and Efficiency. Data were gathered through interviews with 23 key and supporting informants, passive participatory observation, and document analysis. The results reveal that PANAH SRIKANDI successfully facilitates digital transformation in population administration services at the village level. Political support, skilled human resources, and strategic partnerships emerged as key enablers, while infrastructure and digital literacy barriers are addressed through continuous training and cross-sector collaboration. This study highlights that digital public service implementation at the local level requires adaptive strategies and strong, sustained commitment from all stakeholders involved.